Adoption of Proprietary Online Education Software Compared to Free And Open-Source Software in Indian colleges (Journal of Information Technology and Digital World, 2022)
Adoption of online learning tools is still in the nascent stage in India. Use of such tools has been sporadic and patchy at best. The Covid pandemic of 2020 forced the institutions to shut down which resulted in the sudden adoption of such software. The education market in India is dominated by free & open-source software also known as FOSS while proprietary software solutions take a back seat. This research focuses on the impacts of proprietary education software in easing the learning process for children as well as grad-students, and how these tools impact engagement and learnability. Moreover, a retrospective study of an open-source tool present in the market and the comparison of it with the proposed system have been presented. Further, an example of a proposed system of how a simple system can be created in-house and at minimal cost to serve as a proprietary solution for all online educational needs of the pupils has been demonstrated.
Keywords: Proprietary; Open-source; Education; Software; Covid-19; pandemic; FOSS; BBDLearn